2013
DOI: 10.1155/2013/305081
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Interaction between Isoimperatorin and Human Serum Albumin by Multispectroscopic Method: Identification of Possible Binding Site of the Compound Using Esterase Activity of the Protein

Abstract: Isoimperatorin is one of the main components of Prangos ferulacea as a linear furanocoumarin and used as anti-inflammatory, analgesic, antispasmodic, and anticancer drug. Human serum albumin (HSA) is a principal extracellular protein with a high concentration in blood plasma and carrier for many drugs to different molecular targets. Since the carrying of drug by HSA may affect on its structure and action, we decided to investigate the interaction between HSA and isoimperatorin using fluorescence and UV spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…The amide I peak position occurs in the region 1600-1700 cm −1 and the amide II band 1500-1600cm −1 . Amide I band is more sensitive to the change of protein secondary structure than amide II [32,33]. Figure 2 shows the FT-IR spectrum of free MMP9 and the FT-IR spectra after binding with GBA.…”
Section: Ft-irmentioning
confidence: 99%
“…The amide I peak position occurs in the region 1600-1700 cm −1 and the amide II band 1500-1600cm −1 . Amide I band is more sensitive to the change of protein secondary structure than amide II [32,33]. Figure 2 shows the FT-IR spectrum of free MMP9 and the FT-IR spectra after binding with GBA.…”
Section: Ft-irmentioning
confidence: 99%
“…During a fluorescence titration experiment at the wavelength of excitation or at the wavelengths used to follow an emission, the absorption of the molecule added resulted in a spurious decrease in the observed fluorescence intensity [11]. In the steady-state fluorescence experiments, absorption spectrum of drugs overlaps with the excitation and emission of proteins.…”
Section: The Inner Filter Effectmentioning
confidence: 99%
“…The binding of drugs to plasma proteins (especially albumin) affects their distribution and rate of metabolism [10]. Crystal structure analyses have revealed that HSA has two hydrophobic pockets as binding sites for aromatic and heterocyclic ligands; one site in subdomain IIA (commonly referred to as Sudlow's site I: warfarin-binding site) and the other within subdomain IIIA (commonly referred to as Sudlow's site II: indole/ benzodiazepine site) [11]. Both hydrophobic and electrostatic interactions play a major role in controlling the affinity towards drug binding for sites I and II; for site I, mainly hydrophobic interactions are dominant, whereas for site II, a combination of hydrophobic, hydrogen bonding, and electrostatic interactions all play a crucial role [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interactions among small molecules, drugs, and surfactants with proteins have been studied extensively, particularly the structural aspects, because it is important to elucidate the molecular aspects of binding to establish the structure–function relationship on the one hand and drug design and efficacy on the other hand . In particular, affinity, toxicity, and structural modifications of serum proteins have been studied to determine the efficacy of drug distribution in the target sites.…”
Section: Introductionmentioning
confidence: 99%